The Ethnobotany and Potential of Sugar Palm (Arenga pinnata Merr.) on The Kasepuhan Pasir Eurih Community, Sindanglaya Village, Lebak Regency, Banten - Nira Febriyanti; Agus Hikmat; Ervizal A. M. Zuhud (Media Konservasi, 2017)
Sugar palm (Arenga pinnata Merr.) is one type of palm that has the potential of high ecological and economic value. This study aimed to identify the ethnobotany of sugar palm, analyzes habitat vegetation conditions, regeneration rate and spatial distribution of sugar palm in Kasepuhan Pasir Eurih. The method used is in-depth interview with informant selection using purposive sampling technique, vegetation analysis, observation and literature study. The greatest utilization is found in the male flower portion for tapping the water of nira as a raw material for making palm sugar. Sugar palm often found in the research location is sugar palm at the level of stake. The level of sugar palm regeneration in Kasepuhan Pasir Eurih is quite sustainable. The pattern of spatial spread of sugar palm in Kasepuhan Pasir Eurih is spread and located at an altitude of 500-600 masl as well as grow wild in the forest. The most common plant species found around sugar palm is africa (Maesopsis eminii) which on average has the largest Important Value Index (IVI) after sugar palm.Keywords: ethnobotany, kasepuhan community, regeneration, sugar palm